In vitro study on interaction of ketotifen fumarate with metformin hydrochloride - Sayeed, Mohammed Aktar; Hasan, S. M. Raquibul; Rana, Md Sohel (© 2011 Latin American Journal of Pharmacy, 2016)
This article was published in Latin American Journal of Pharmacy [© 2011 Latin American Journal of Pharmacy] and the definite version is available at: https://goo.gl/XOJ7tm